2016
DOI: 10.1093/sf/sow040
|View full text |Cite
|
Sign up to set email alerts
|

Race, Marital History, and Risks for Stroke in US Older Adults

Abstract: Stroke is among the leading causes of disability and death in the United States, and racial differences are greater for stroke than for all other major chronic diseases. Considering the equally sizeable racial disparities in marital life and associated risks across adulthood, the current study hypothesizes that black-white differences in marital history play an important role in the large racial inequalities in the incidence of stroke. The major objective are to (i) demonstrate how marital history is associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
22
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 100 publications
6
22
1
1
Order By: Relevance
“…This association is also evidenced by other studies 2,11,12,[22][23][24] and points to a healthier lifestyle associated with marriage as a likely cause of the lower risk of stroke. Nonetheless, there seems to be sufficient evidence for assuming that marriage is the superior form of living arrangement when it comes to risk of stroke.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…This association is also evidenced by other studies 2,11,12,[22][23][24] and points to a healthier lifestyle associated with marriage as a likely cause of the lower risk of stroke. Nonetheless, there seems to be sufficient evidence for assuming that marriage is the superior form of living arrangement when it comes to risk of stroke.…”
Section: Discussionsupporting
confidence: 73%
“…In studies from USA 11,12 with adjustments similar to those in our study, the never-married and widowed but not the TA B L E 1 Number of person-years, incident events, and incidence of stroke by marital status divorced had higher risk of stroke in one study 11 while in another 12 risks of stroke were higher in persons who were currently divorced, remarried, and widowed. In studies from USA 11,12 with adjustments similar to those in our study, the never-married and widowed but not the TA B L E 1 Number of person-years, incident events, and incidence of stroke by marital status divorced had higher risk of stroke in one study 11 while in another 12 risks of stroke were higher in persons who were currently divorced, remarried, and widowed.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…A second notable finding is that marital timing has no association with survival after a heart attack. Other studies have demonstrated significant risks associated with early marriage and disease incidence (Dupre 2016; Zhang and Hayward, 2006); however, this study suggests that marriage timing does not influence the likelihood of dying following the onset of a major cardiovascular event. Although more research is needed to further substantiate these results, this finding is consistent with demonstrating the importance of marital factors that are most proximate to the health event.…”
Section: Discussioncontrasting
confidence: 76%
“…Divorce and widowhood also bring a decline in the availability of social and financial resources (Ross, Mirowsky, and Goldsteen, 1990; Wilmoth and Koso, 2002). Indeed, studies show that divorce and widowhood transitions increase a person’s risk of disease, disability, and death (Hemström, 1996; Pienta, Hayward, and Jenkins, 2000; Zick and Smith, 1991) and that repeated marital losses can be especially detrimental to health and well-being (Barret, 2000; Dupre, 2016; Marks and Lambert, 1998). …”
Section: Introductionmentioning
confidence: 99%